Autogynephilia: A scientific review, feminist analysis, and alternative 'embodiment fantasies' model. Issue 4 (July 2020) - Serano, Julia
It is generally accepted within psychology and among trans health providers that transgender people who transition do so because they have a gender identity that is incongruent with their birth-assigned sex, and distinct from their sexual orientation. In contradiction to this standard model, the theory of autogynephilia posits that transgender women's female gender identities and transitions are merely a by-product of their sexual orientations. While subsequent research has yielded numerous lines of evidence that, taken together, disprove the theory, autogynephilia is still often touted by anti-transgender groups, including trans-exclusionary feminists. Here, I provide an updated overview of the scientific case against autogynephilia. Following that, I will forward an alternative 'embodiment fantasies' model that explains all the available findings better than autogynephilia theory, and which is more consistent with contemporary thinking regarding gender and sexual diversity. I will also demonstrate how autogynephilia theory relies on essentialist, heteronormative, and male-centric presumptions about women and LGBTQ+ people, and as such, it is inconsistent with basic tenets of feminism.